Constraints to biofuel feedstock production expansion in Zambia - Paul C. Samboko; Mulako Kabisa; Giles Henley (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
World biofuel production has been increasing to improve energy security and mitigate global warming. Southern Africa's bioenergy demand could increase with South Africa's planned fuel blending mandates, triggering increased demand for feedstocks and agricultural land. Ensuring sustained production will require a full understanding of the constraints to production expansion, considering the tradeoffs that may be generated in rural areas, as has been observed for large-scale land acquisitions. We analyse the social and biophysical constraints to biofuel production expansion in Zambia. Previously social constraints have received limited attention even though they may prove more problematic. Results indicate that Zambia is at least moderately suitable for bioenergy investments with biophysically suitable areas largely coinciding with the socially suitable areas. However, existing gaps in compensatory procedures may inhibit large-scale projects' access to development finance if not aligned with internationally acceptable practices, and generate negative outcomes if safeguards are not in place.
Keywords: N77; O13; Q15; Q16; 330; biofuels; social constraints; biophysical constraints; Zambia; Southern Africa